Infidelidade e barbárie na Hispania visigoda - Frighetto, Renan (Gerión. Revista de Historia Antigua, 2002)
Hispanic-roman and visigothic manuscripts have a characterization of the barbarians that is well known in recent historiography. However, such characterization is absent in juridical texts, mainly in the seventh century. The objective of this study is to discuss the hypothesis that the word «unfaithful» substitutes for «barbarian» in these texts, once the characterization of both is quite similar.